Study of the impurities influence on the electrical conductivity of apatites: the CaHAp case - Espinoza, R. M. (2012)
In the present work we study the temperature dependence of the electrical conductivity of apatites. For this purpose, we propose a spectral conductivity model which takes into account the most relevant characteristics of the material analyzed. The electrical conductivity obtained from this model is in good agreement with experimental data measured by Laghzizil et. al [1]. Additionally, we also observe an increment of the electrical conductivity, in the range from 1000 to 1300℃) after including impurities in the system.